Analisis Aksesibilitas Website Pemerintah Provinsi di Indonesia Menggunakan Pedoman Web Content Accessible Guidelines 2.0 - Amelia Dwi Deastu; Gita Indah Marthasari; Vinna Rahmayanti Setyaning Nastiti (Universitas Muhammadiyah Malang, 2020)
Web accessibility is people with disabilities to be able to use, navigate, and interact with the website. World Wide Web Consortium (W3C) has provided important guidelines about web accessibility known as the Web Content Accessible Guidelines (WCAG). Indonesian government encourages the use of new media through Presidential Instruction Number 3 of 2003 concerning National Policies and Strategies for e-Government Development which mandates every state institution to build websites. Therefore in this study, an evaluation analysis was carried out on the website of Indonesia Provincial Government by using two accessibility evaluation automation tools namely TAW and aXe. This research presents the main problems found from all provincial government websites based on problems, warnings, and success criteria. With the TAW tool, the highest number of problems found in the Perceivable principle section, which amounts to 6490. And the provincial government sites that have the most accessibility issues based on the TAW tool are East Nusa Tenggara and Riau, while for the aXe tool are Yogyakarta and West Borneo.